Alkaline-thermal pretreatment of spectinomycin mycelial residues: Insights on anaerobic biodegradability and the fate of antibiotic resistance genes. (December 2020) - Song, Siqi; Jiang, Mingye; Yao, Jie; Liu, Huiling; Dai, Xiaohu; Wang, Gang
Abstract: Alkaline-thermal (AT) pretreatment is an economical and efficient pretreatment method to improve anaerobic biodegradability of biowaste. This study investigated the effect of AT pretreatment of spectinomycin mycelial residues (SMRs) for promoting anaerobic biodegradability along with the reduction of antibiotic resistance genes (ARGs), and thus obtained the optimal conditions of AT pretreatment. Biomethane potential (BMP) test was conducted to evaluate the anaerobic biodegradability of untreated and pretreated SMRs, and the fate of ARGs was tracked by quantitative polymerase chain reaction. Results showed that the modified Gompertz model fitted the results of BMP tests satisfactorily. Furthermore, AT pretreatment promoted BMP (B0 ) and reduced lag phase (λ) effectively. These were attributed to the solubilization of SMRs. The analyses of the changes in dissolved organic matter indicated that AT pretreatment could facilitate the solubilization of both biodegradable (e.g. protein) and recalcitrant matter (e.g. humic-like, analyzing by EEMs-PARAFAC), which had a significant corresponding positive (Person correlation, p  < 0.01) and negative (Partial correlation, p  < 0.01) influences on anaerobic biodegradability. However, the positive effects surpassed the negative effects, promoting the overall anaerobic biodegradability of SMRs. In addition, a considerable reduction of ARGs (by 0.62–1.36 log units) was observed at pH ≥ 12, attributed to the hydrolysis of phosphodiester bond of DNA in strong alkaline solution. Considering both anaerobic biodegradability and ARGs, the optimal AT condition was concluded as pH 12, temperature 90 °C and time 120 min. Graphical abstract: Image 1 Highlights: Based on PARAFAC analysis, AT pretreatment accumulated humic-like substances. The modified Gompertz model fitted the results of BMP tests satisfactorily. Partial correlation analysis discerned potential bad effects of humic-like on AD. pH ≥ 12 was proposed to reduce the abundance of ARGs of SMRs in AT pretreatment.